Towards a New 3Rs Era in the construction of 3D cell culture models simulating tumor microenvironment - Zhang, Long; Liao, Weiqi; Chen, Shimin; Chen, Yukun; Cheng, Pengrui; Lu, Xinjun; Ma, Yi (Frontiers in Oncology, 2023)
Three-dimensional cell culture technology (3DCC) sits between two-dimensional cell culture (2DCC) and animal models and is widely used in oncology research. Compared to 2DCC, 3DCC allows cells to grow in a three-dimensional space, better simulating the in vivo growth environment of tumors, including hypoxia, nutrient concentration gradients, micro angiogenesis mimicism, and the interaction between tumor cells and the tumor microenvironment matrix. 3DCC has unparalleled advantages when compared to animal models, being more controllable, operable, and convenient. This review summarizes the comparison between 2DCC and 3DCC, as well as recent advances in different methods to obtain 3D models and their respective advantages and disadvantages.